Czas wolny, turystyka i rekreacja osób niesłyszących w Polsce - zarys specyfiki problemu - Zajadacz, Alina (Wydawnictwo Naukowe UAM, Poznań 2010, 2010)
This study brings closer the problems of a selected group with a handicap – deaf people for whom the main mode of communication is the Polish Sign Language. The subject of studies is leisure time, how it is spent by them both everyday and during vacation. The book presents a survey of literature, good practice and also results of the author’s own studies conducted in the years 2004-2010, concerning problems of tourism and recreation of the deaf. In the years 2008-2010 studies were conducted within the research project financed by Ministerstwo Nauki i Szkolnictwa Wyższego (the Ministry of Science and Higher Education). One of the results of work on this project are multimedia programmes – tourist guides: SITur and SITex containing a translator of the Polish Sign Language.
Keywords: turystyka; głusi; niesłyszący